1992
DOI: 10.1111/j.1600-0714.1992.tb01011.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral‐dental findings in dyskeratosis congenita

Abstract: A 13-yr-old girl with dyskeratosis congenita is presented. Besides oral leukoplakia and nail dystrophies, there was evidence of pancytopenia, growth retardation, alopecia, mental retardation and microcephaly. The oral findings included caries, gingival recession, short-blunted roots, gingival bleeding, tooth mobility and severe alveolar bone loss resembling juvenile periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 19 publications
2
25
2
Order By: Relevance
“…Dental radiographs were not obtainable on the 3 year old with decreased ANC. Other previously reported findings of increased caries, hypodontia and thin enamel (Wald and Diner, 1974; Yavuzyilmaz et al , 1992; Brown, 2000) were not confirmed in this study. Given the heterogeneous nature of this patient group, these findings might be found in a larger study of patients and appropriate controls.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Dental radiographs were not obtainable on the 3 year old with decreased ANC. Other previously reported findings of increased caries, hypodontia and thin enamel (Wald and Diner, 1974; Yavuzyilmaz et al , 1992; Brown, 2000) were not confirmed in this study. Given the heterogeneous nature of this patient group, these findings might be found in a larger study of patients and appropriate controls.…”
Section: Discussioncontrasting
confidence: 99%
“…Several case reports have described specific oral changes in association with DC. These include oral leukoplakia, increased dental caries, hypodontia, thin enamel structure, aggressive periodontitis, intraoral brown pigmentation, tooth loss, taurodontism and blunted roots (Wald and Diner, 1974; Loh et al , 1987; Yavuzyilmaz et al , 1992; Handley and Ogden, 2006). To establish the phenotypes of various IBMFS, including DC, the Clinical Genetics Branch of the National Cancer Institute (NCI) is extensively evaluating patients and family members with these disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Oral manifestations-Oral, dental, and periodontal manifestations reported are leukoplakia, decreased dental crown-to-root ratio, tooth taurodontism, and early-onset aggressive periodontal disease (Wald and Diner, 1974;Yavuzyilmaz et al, 1992;Atkinson et al, 2008). Atkinson et al detected oral leukoplakia in 65% of their study population, predisposing these individuals to oropharyngeal carcinoma (Atkinson et al, 2008).…”
Section: Treatment-optimal Treatment For Patients With Dkc Is Hct Fromentioning
confidence: 99%
“…However, intracellular edema is not pathognomonic for WSN; in fact, the same aspect is present in other lesions, such as the leukoedema which is quite similar to WSN, even if it shows no parakeratosis 6. When we manage a patient affected by WSN no treatment is required onto these lesions, except for a clinical condition of a plaque which extends onto the lip vermilion: in this kind of cases, we perform a surgical exeresis for aesthetic reasons 7.…”
Section: Introductionmentioning
confidence: 99%